Effects of Catalysts on the Structure and Piezoelectric Properties of PVDF/ZnO Nanowires for the Robotic Tactile Sensor - Ming-Cheng Kao; Jun-Hong Weng; Chih-Hung Chiang; Kai-Huang Chen; Tsung-Kuei Kang (Engineering Proceedings)
Polyvinylidene fluoride (PVDF)-coated ZnO nanorod piezoelectric sensors were prepared on silicone-based polymer polydimethylsiloxane (PDMS) substrates using a hydrothermal method. The effects of catalysts (sodium hydroxide, ammonium hydroxide, and hexamethylenetetramine) on the lattice microstructure and piezoelectric properties of ZnO nanorods were analyzed. The piezoelectric properties of polyvinylidene fluoride-coated ZnO nanorods’ tactile sensors with different catalysts were measured under different forces. ZnO nanorods with hexamethylenetetramine have a high c-axis (002)-preferred orientation hexagonal wurtzite crystal structure with a maximum length of 5800 nm and an aspect ratio of 72.5. The Polyvinylidene fluoride/ZnO nanorod sensor with hexamethylenetetramine showed an excellent linear response to external pressure in the range of 0.1~1.2 N, and the best sensitivity is 61.1 mV/N.